2016
DOI: 10.24297/jac.v12i2.2154
|View full text |Cite
|
Sign up to set email alerts
|

TiO2- CuI Nanoparticle /Ru Solid State Dye-Sensitize Solar Cells

Abstract: In this work  solid state dye sensitized solar cell (SSDSSC) type  (ITO / TiO2/ Ru / CuI / Ag) is fabricated. The thin films are prepared by pulse laser deposition (PLD) technique under the vacuum pressure of 3×10−3 mbar and annelid at 450 oC. In this technique  Nd:YAG laser at 1064 nm wavelength with (200 , 500 , 800) pulsed was used. It was noticed from (I-V) characteristics of the solar cell that  the photocurrent  collected  from  the  TiO2  (NP)  is increase as the number of  laser pulses increase. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, efficiencies that were reported in subsequent studies did not improve any further, and they ranged from 1–5.5% at most [340,341,342,343,344]. In 2014, Amalina and Rusop conducted an investigation into the properties of CuI thin films [340].…”
Section: Electrolytes For Dsscsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, efficiencies that were reported in subsequent studies did not improve any further, and they ranged from 1–5.5% at most [340,341,342,343,344]. In 2014, Amalina and Rusop conducted an investigation into the properties of CuI thin films [340].…”
Section: Electrolytes For Dsscsmentioning
confidence: 99%
“…Taha et al demonstrated the effect of pulse laser deposition (PLD) for both TiO 2 and the CuI thin films on the performance of ss-DSSCs [342]. The thin films were fabricated by PLD under 3 × 10 −3 mbar of vacuum pressure and annealed at 450 °C.…”
Section: Electrolytes For Dsscsmentioning
confidence: 99%
See 1 more Smart Citation